2014
DOI: 10.4081/mrm.2014.371
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing disorders in tracheostomised patients: a multidisciplinary/multiprofessional approach in decannulation protocols

Abstract: Safe removal of tracheal cannula is a major goal in the rehabilitation of tracheostomised patients to achieve progressive independence from mechanical support and reduce the risk of respiratory complications. A tracheal cannula may also cause significant discomfort to the patient, making verbal communication difficult. Particularly when cuffed, tracheal cannula reduces the normal movement of the larynx which can further compromise the basic swallowing defect. A close connection betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 0 publications
0
11
1
4
Order By: Relevance
“…They speculated that these functions had really regained better than had been predicted from the initial assessment and earlier and safe decannulation can be done when FEES is applied [9]. Decannulation could be probable in certain cases of patients in a vegetative or in a minimally conscious state after confirming a patent airway, effective cough, and spontaneous swallowing that could be proved by endoscopic assessment and not by bedside assessment [20].…”
Section: Discussionmentioning
confidence: 99%
“…They speculated that these functions had really regained better than had been predicted from the initial assessment and earlier and safe decannulation can be done when FEES is applied [9]. Decannulation could be probable in certain cases of patients in a vegetative or in a minimally conscious state after confirming a patent airway, effective cough, and spontaneous swallowing that could be proved by endoscopic assessment and not by bedside assessment [20].…”
Section: Discussionmentioning
confidence: 99%
“…These complications demands a multidisciplinary team approach, with good coordination between its team members, for evaluation and rehabilitation to ensure the safety and quality care of these patients. 10,11 In a study, Mah et al concluded that, "the introduction of care bundle for post tracheostomy care to the multidisciplinary tracheostomy service significantly improve oral diet intake as well as decannulation". 12 Thus restoration of function of respiration, phonation, feeding and swallowing demands a strict integration and participation among different members of the multidisciplinary rehabilitation team.…”
Section: Discussionmentioning
confidence: 99%
“…9 Hence tracheostomy tube results in difficulty in verbal communication and reduction in laryngeal movement results in further compromise in swallowing. 10 Also tracheostomy has been note d as an independent risk factor for development of aspiration and dysphagia. 4 Extensive neurorehabilitation is required since patients with surgical airway may develop swallowing difficulties including dysphagia and / or aspiration with a very high prevalence, which can pose a threat to life.…”
Section: Review Articlementioning
confidence: 99%
“…The removal of the tracheal cannula is also an important objective in the rehabilitation of tracheostomized patients to achieve the progressive independence of mechanical ventilatory support and reduce the risk of respiratory complications [13]. Decannulation not only involves removal of the TQT cannula, but also evaluation of permeability and protection of the upper airway [14].…”
Section: Case Reportmentioning
confidence: 99%